2020
DOI: 10.1038/s41598-020-61691-y
|View full text |Cite
|
Sign up to set email alerts
|

Marine virus predation by non-host organisms

Abstract: Viruses are the most abundant biological entities in marine environments, however, despite its potential ecological implications, little is known about virus removal by ambient non-host organisms. Here, we examined the effects of a variety of non-host organisms on the removal of viruses. The marine algal virus PgV-07T (infective to Phaeocystis globosa) can be discriminated from bacteriophages using flow cytometry, facilitating its use as a representative model system. Of all the non-host organisms tested, anem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 79 publications
2
30
0
Order By: Relevance
“…It is widely established that such similarities to holobiont virome studies should be treated with caution, as the viruses reported could in fact be infecting symbionts, eukaryotic parasites, or bacteria that are also present in these samples . Marine invertebrate organisms are also important ocean filters and virus removers 74 , again compatible with the idea that at least some of the viruses identified here may infect other marine organisms.…”
Section: Limitations To Virus Discovery and Inferring Virus-host Relationshipssupporting
confidence: 86%
“…It is widely established that such similarities to holobiont virome studies should be treated with caution, as the viruses reported could in fact be infecting symbionts, eukaryotic parasites, or bacteria that are also present in these samples . Marine invertebrate organisms are also important ocean filters and virus removers 74 , again compatible with the idea that at least some of the viruses identified here may infect other marine organisms.…”
Section: Limitations To Virus Discovery and Inferring Virus-host Relationshipssupporting
confidence: 86%
“…Recently, due to COVID problematic, studies on antiviral activity of poriferan secondary metabolites are in trend. The ability of marine demosponges to collect viruses in their bodies due to their water filtering activity is well recognized [ 95 , 96 ]. How sponges neutralize viruses is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Strong indications of virus ingestion falling on specific taxa, and notably higher abundances of viruses within Choanozoa SAGs, averaging 28 viral sequences per cell, suggests that the degree of viral loss due to protist predation would be variable and dependent upon protist community structure. A recent study demonstrated the efficient removal of planktonic viruses by marine sponges, highlighting a need to reconsider viral predation by non-host organisms even among metazoans ( Welsh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%